PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL STORYTELLING TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI - Ubaidillah; Desy Rahma Agustin; Ismi Khoirun Nisa; Nabila Aulia; Elvira Rossa Hidayah (LPPM IAD Probolinggo, 2026)
Language development is one of the most important aspects of early childhood education that requires appropriate stimulation through engaging and child-centered learning activities. However, the continued use of conventional teaching methods often limits the optimal development of children's language skills. This study aimed to examine the effect of using Digital Storytelling as a learning medium on the language development of early childhood learners. The research employed a quantitative approach using a Pre-Experimental One-Group Pretest–Posttest Design. The participants consisted of 35 children aged 5–6 years in Group B at RA H. Achmad Ali. Data were collected through an observation checklist based on the indicators of the Early Childhood Development Achievement Standards (STPPA). Data analysis was conducted using descriptive statistics and a Paired Sample t-Test to determine differences in language development before and after the intervention. The findings revealed a significant improvement in children's language skills following the implementation of Digital Storytelling. The posttest mean score was higher than the pretest mean score, and the t-test results showed a significance value of less than 0.05, indicating a statistically significant effect. Therefore, Digital Storytelling was found to be an effective learning medium for enhancing early childhood language development, particularly in listening skills, vocabulary acquisition, story comprehension, and story retelling abilities.